Threats to Press Freedom: an Analysis of the Terror Campaign Targeting Tempo Magazine In the Context of Press Freedom and Political Dynamics In Indonesia - Nuris Watunnaba Watunnaba (LPPM Universitas PGRI Sumatera Barat, 2024)
This article examines threats to press freedom as a vital space for expressing public opinion and as a foundational pillar of democracy, alongside the executive, legislative, and judicial branches. It approaches the issue of threats to press freedom through Gramsci’s concept of hegemony, wherein the ruling class’s dominance indirectly influences and controls the press by shaping acceptable cultural values and ideologies. However, the state at times also employs coercive elements through its institutional role, thereby posing additional threats to press freedom. The objective of this study is to explain and interpret Gramsci’s perspective on threats to press freedom within democratic states. Employing a qualitative method and a discourse analysis approach, the research draws upon Tempo magazine as a case study of press freedom under threat. The author argues that the state indirectly shapes press freedom through policies that conflict with democratic values, and that such hegemonic influence over the press reveals a governance framework rooted in the principle of non-neutrality.